Cigarette smoking and hormones. Issue 4 (August 2016) - Marom-Haham, Lilach; Shulman, Adrian
Abstract : Purpose of review: The purpose is to provide a summary of the effects of cigarette smoking on steroid hormone metabolism and how it affects female fertility. Recent findings: Components of tobacco smoke such as polycyclic aromatic hydrocarbons lead to transcriptional upregulation of a number of genes, including members of the cytochrome P450 (CYP) family, in particular CYP1B1 and CYP1A1. In humans, CYP1A1 and CYP1A2 are the primary enzymes catalyzing the 2-hydroxylation of estradiol. This pathway shunts available estrogen away from the more estrogenically potent 16α-hydroxylation to the production of catechol estrogens, mainly 2 and 4 hydroxyestradiol. Summary: Smoking has multiple effects on hormone secretion and metabolism. These effects are mainly mediated by the pharmacological action of tobacco alkaloids (nicotine and its metabolite cotinine). A strong body of evidence indicates that the negative effects of cigarette smoking on fertility compromises nearly every system involved in the reproductive process.